Kajian Kriminologis Tentang Persetubuhan Dengan Anak Bedasarkan Undang-Undang Perlindungan Anak (Studi Kasus Kabupaten Alor) - Ahmad, Rahmawati; Leo, Rudepel Petrus; Dima, Adrianus Djara (Artemis Law Journal, 2025)
Sexual intercourse is a sexual relationship between two people conducted with mutual consent. However, in the legal context, sexual intercourse can also refer to sexual relations between an adult and a minor who is considered unable to give valid consent. The results of this study indicate: (1) The factors influencing the occurrence of sexual intercourse with children are internal and external factors. The first internal factors are: (a) The psychological condition of the perpetrator, (b) The biological condition of the perpetrator, (c) The ability to manipulate psychologically and the perpetrator's speaking skills. The second external factors are: (a) The religious environment that is closed in supervision, (b) The misuse of status as a religious leader, (c) Modus operandi based on religious manipulation, (d) Lack of supervision of children, (e) The influence of pornography. (2) Efforts to tackle the crime of rape are carried out in three ways: (a) Preemptive efforts are made through socialization by the Binmas Unit, the formation of children's forums by the PPA Office, and legal education. (b) Preventive efforts are made through supervision by the PPA Reskrim Unit, the formation of the Child Protection Task Force, and cooperation with the Health Office and Hospitals for victim rehabilitation. (c) Repressive efforts are made through law enforcement by the PPA Reskrim Unit, victim assistance by the PPA Office, and the application of maximum punishment by the Kalabahi District Court.